2009
DOI: 10.1111/j.1537-2995.2009.02293.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14 new alleles at the fucosyltransferase 1, 2, and 3 loci in Styrian blood donors, Austria

Abstract: Multiple common and sporadic sequence variations including 14 new alleles at FUT1, FUT2, and FUT3 loci were identified. Four novel mutations result in amino acid substitution in the protein. Three of them are predicted to have adverse effects on the enzyme activity. A novel nonsecretor allele was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 60 publications
(73 reference statements)
2
21
0
Order By: Relevance
“…The fucosyltransferase gene family encodes enzymes that transfer fucose from α(1,2), α(1,3/4) and α(1,6) linkages to various glycans. FUT1 and FUT2 encode α(1,2)-fucosyltransferases, which transfer a terminal fucose residue from an α(1,2)-linkage to an existing galactose Type 1 or 2 precursor substance and form the H1 or H2 antigen as precursors of soluble ABH antigens, respectively (4). FUT1 is ubiquitously expressed in the human body and preferentially expressed in erythroid tissues and vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fucosyltransferase gene family encodes enzymes that transfer fucose from α(1,2), α(1,3/4) and α(1,6) linkages to various glycans. FUT1 and FUT2 encode α(1,2)-fucosyltransferases, which transfer a terminal fucose residue from an α(1,2)-linkage to an existing galactose Type 1 or 2 precursor substance and form the H1 or H2 antigen as precursors of soluble ABH antigens, respectively (4). FUT1 is ubiquitously expressed in the human body and preferentially expressed in erythroid tissues and vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…FUT1 is ubiquitously expressed in the human body and preferentially expressed in erythroid tissues and vascular endothelial cells. FUT2 is mainly expressed in the epithelial cells of the digestive and respiratory tracts (4). FUT3 - FUT7 and FUT9 encode α(1,3)-fucosyltransferases, and their gene products transfer a fucose residue from an α(1,3)-linkage to galactose in H1 and H2 antigens to produce various Lewis antigens (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In Lewis-positive individuals, the secretor status is deduced from the Lewis phenotype, i.e., Le(a-b+) individuals are secretors, and Le(a+b−) individuals are nonsecretors [10]. Several single-base mutations have been identified in a number of Lewis-negative individuals of various ethnic groups [6,9,11,12]. Salomaa et al [13] reported that 90% to 95% of Lewis-negative individuals could be identified by screening for the single nucleotide polymorphisms (SNPs) T59G, T1067A, T202C, and C314T, and these four SNPs appear to be common in the population at large.…”
Section: Introductionmentioning
confidence: 99%
“…a), suggesting the deletion of FUT2 gene in Bombay phenotype using the primers by Matzhold et al . . A 1·8‐kb fragment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…, while the FUT2 gene was amplified as described by Matzhold et al . . FUT2 gene was also amplified by GAP‐PCR using the primers described by Pang et al .…”
Section: Methodsmentioning
confidence: 99%